Accelerating crop improvement through genome editing reporting period: From starting date to DEC, 2025 - Chavarriaga, Paul; Sanchez, Francisco Jose (2025)
As a center participating in the Gene Editing Initiative, the Alliance of Bioversity International and CIAT contributes to WP1 and WP2 of the GEDi project. The REDBIO 2025 event, held in Medellín, Colombia, from September 9 to 11, served as a key platform to explore the intersection of biotechnology, the bioeconomy, and DeepTech innovations. In this context, the Communications Team developed and implemented a comprehensive strategy to highlight institutional participation, strengthen the visibility of key scientific initiatives, and promote scientific outreach using accessible and engaging formats for diverse audiences here.